2014
DOI: 10.1590/s0100-736x2014000200013
|View full text |Cite
|
Sign up to set email alerts
|

Aspecto radiológico e macroscópico de matriz óssea mineralizada heteróloga fragmentada e polimetilmetacrilato autoclavados em falha óssea de tíbia de coelho

Abstract: Pesq. Vet. Bras. 34(2):173-178, fevereiro 2014 173 RESUMO.-Foi realizada falha segmentar com 6mm de diâ-metro na região metafisária medial de tíbias de 12 coelhos, onde foi implantado uma associação de micro e macrofragmentos de matriz óssea cortical heteróloga fragmentada conservada em glicerina (98%) e polimetilmetacrilato autoclavados, para a sua reconstrução, e avaliados radiológi-ca e macroscopicamente aos 30, 60, 90 e 120 dias. Houve adesão, em relação ao tempo, dos micro e macrocompósi-tos ao leito rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
19

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 20 publications
2
6
0
19
Order By: Relevance
“…The observed bone growth interruption lines show abrupt discontinuation of osteoid matrix production and subsequent recovery, as described previously 13,27 . However, in this study, no local inflammatory infiltrate was observed, but only coarse and porous trabecular formation, without osteoblasts.…”
Section: ■ Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The observed bone growth interruption lines show abrupt discontinuation of osteoid matrix production and subsequent recovery, as described previously 13,27 . However, in this study, no local inflammatory infiltrate was observed, but only coarse and porous trabecular formation, without osteoblasts.…”
Section: ■ Discussionsupporting
confidence: 81%
“…It is evident that angiogenesis is evident in the trabecular bone, indicative of the acute phase of bone repair, with osteoid matrix structuring of immature braided osteophyte immediately adjacent to the blood vessels and massive infiltration of active osteoblasts, suggesting that they are responsible for matrix deposition. These characteristics suggest an intensification of the bone repair process, in the remodeling phase, since no inflammatory infiltrate was identified, as described previously 13,27 .…”
Section: ■ Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Além, desses dois métodos, a esterilização também pode ser realizada com o uso de autoclave, que foi a técnica utilizada neste estudo para esterilizar os corpos de prova , Moreira et al 2014.…”
Section: Resultsunclassified
“…Apesar de serem biologicamente inferiores ao biomaterial autógeno, eles têm sido bastante utilizados na ortopedia reparadora, com resultados satisfatórios (Lane & Sandhu 1987, Moraes et al 2004, Tadjoedin et al 2003, Carneiro et al 2005, Freitas et al 2008. As falhas ósseas também podem ser completa e eficientemente preenchidas por biomateriais sintéticos, como polimetilmetacrilato (Kawano et al 1998, Weinfeld et al 1999, Rahal et al 2000, Braz et al 2003, Moreira et al 2014.…”
Section: Introductionunclassified